Distribusi Harta Milik Negara Perspektif Ibn Taimiyah - Juliandi , Budi; Khairuddin, Muhammad Khairuddin (STAINI Press, 2024)
Normatively, the provisions regarding the distribution of state property in Islam have been regulated in the Quran. However, for an interest, the distribution turned out to be done outside of what was mentioned by nas. This study explores Ibn Taymiyyah's thoughts on the distribution of state property that are not explicitly mentioned by nas. This is a literary study that explores Ibn Taymiyah's economic thought. The main source of this research is Ibn Taymiyyah's work entitled al-Siyasah al-Shar'iyyah fi-Ishlah al-Ra'i wa al-Ra'iyyah. The study concluded that state property could be given to the elite of society (ru'asa'). The elite of society in question is the elite of the society both of non-Muslim societies and of the elites of Muslim societies